‘Sho't left': understanding the factors influencing public transportation mode choice with a focus on minibus taxis and MyCiTi in Dunoon, Cape Town - Mogotsi, Dineo (Department of Environmental and Geographical Science, 2025)
This research explores the factors influencing public transportation mode choice with a focus on minibus taxis and the MyCiTi bus rapid transit system in Dunoon, Cape Town. The research aims to understand the advantages and disadvantages of each mode. Despite the long-standing concerns about minibus taxi drivers' conduct, road safety, overloading, and vehicle conditions, minibus taxis remain a critical part of South Africa's public transportation system, serving approximately 15 million passengers daily. The research was conducted in Dunoon, a township in Cape Town in the Western Cape province. The study employed a qualitative data collection methodology involving semi structured interviews and participant observation. Thematic analysis, a technique for identifying and interpreting recurring themes within the data, was used to analyse the gathered data. Two theoretical frameworks, paratransit, and bus rapid transit guided the study's investigation. The study's findings indicate that affordability, accessibility, time, safety, and ease of use are all significant considerations for passengers. Minibus taxis emerged as the most popular mode of public transportation in Dunoon due to their speed, affordability, convenience, flexibility, social cohesion, and lack of viable alternatives. This contrasts with the MyCiTi bus service, which, despite its punctuality, lags minibus taxis in popularity due to longer travel times, route limitations, overcrowding, communication issues, and payment system glitches. The study concludes that a hybrid transport governance model, combining care-based and efficiency-driven values, such as social cohesion, offers the most sustainable approach for enhancing commuter journeys in Dunoon. Furthermore, the study suggests that the National Transport Survey should incorporate aspects such as social cohesion and accessibility to measure passenger satisfaction rather than solely focusing on aspects informed by scheduled formal transport. By acknowledging the socio-economic role of minibus taxis in urban transport ecosystems, this research contributes to the discourse on integrating paratransit services like minibus taxis into formal public transportation frameworks, ultimately supporting more inclusive and sustainable urban transport policies in African cities.